The Effect of Career Development and Work-Life Balance on Employee Productivity - Arilawati, Deppy; Mohyi, Achmad; Fuadiputra, Iqbal Ramadhani (Jurnal Manajemen Bisnis dan Kewirausahaan, 2023)
The purpose of this study is to determine the effect of career development and work-life balance on employee work productivity. The type of research used is quantitative research. Data collection by distributing questionnaires using 60 respondents. The data analysis technique uses a range of scale analysis and multiple linear regression analysis. Testing the research hypothesis using partial testing (t-test) and simultaneous testing (F-test). The research results explain career development in the good category, work-life balance in the very good category and work productivity in the very high category. Career development has a significant effect, work-life balance has a significant effect. The simultaneous influence of career development and work-life balance has a significant effect on employee work productivity. It can be concluded that the better the career development and work-life balance, the higher the level of employee productivity.